2014
DOI: 10.1186/1476-511x-13-52
|View full text |Cite
|
Sign up to set email alerts
|

A novel lipoprotein lipase gene missense mutation in Chinese patients with severe hypertriglyceridemia and pancreatitis

Abstract: BackgroundAlterations or mutations in the lipoprotein lipase (LPL) gene contribute to severe hypertriglyceridemia (HTG). This study reported on two patients in a Chinese family with LPL gene mutations and severe HTG and acute pancreatitis.MethodsTwo patients with other five family members were included in this study for DNA-sequences of hyperlipidemia-related genes (such as LPL, APOC2, APOA5, LMF1, and GPIHBP1) and 43 healthy individuals and 70 HTG subjects were included for the screening of LPL gene mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 21 publications
2
25
0
Order By: Relevance
“…The encoded APOA1 protein is a cofactor for the lecithin cholesterol acyltransferase, which plays an important role in the cholesterol reverse transport by promoting its efflux from tissue to the liver for excretion. Notably, another gene at the same locus, APOA5, has been previously associated with hTG, and both genes have been concomitantly implicated in the disease (13,(36)(37)(38)(39)(40). Hence, the strong link of this variant to hTG observed in this study unequivocally points to a central role for the APOA1 gene in this disorder.…”
Section: Discussionsupporting
confidence: 65%
“…The encoded APOA1 protein is a cofactor for the lecithin cholesterol acyltransferase, which plays an important role in the cholesterol reverse transport by promoting its efflux from tissue to the liver for excretion. Notably, another gene at the same locus, APOA5, has been previously associated with hTG, and both genes have been concomitantly implicated in the disease (13,(36)(37)(38)(39)(40). Hence, the strong link of this variant to hTG observed in this study unequivocally points to a central role for the APOA1 gene in this disorder.…”
Section: Discussionsupporting
confidence: 65%
“…Several common variant association studies (CVASs) formerly called genome-wide association studies (GWASs), resequencing and targeted approaches have revealed a wealth of information on the genetic basis for dyslipidemia, and several predisposing genes identified thus far have been implicated in hypercholesterolemia (4-6), hypertriglyceridemia (7)(8)(9)(10)(11)(12)(13) or low HDL-cholesterol levels (14)(15)(16)(17)(18). Despite the volume of these data on dyslipidemia-related genes, only a fraction of the heritability of the disease traits has been explained thus far, and the predisposing gene variants, particularly for LHDLC, are far from being completely unraveled (19).…”
mentioning
confidence: 99%
“…More than 100 mutations in the LPL gene significantly impairing enzyme activity are described [4], many of these are intensively studied in the context of their relationship with hereditary lipid metabolism disorders and acute pancreatitis developing against this background [6,7,9]. In particular, in Chinese population the association between the L279V, A98T [7], L252V, and С264T mutations in LPL gene with HTG development and severity of acute pancreatitis was revealed. The most commonly studied polymorphisms of LPL gene affecting blood triglyceride content are S477X (rs328), PvuII (rs285), and HindIII (rs320) [9].…”
Section: Resultsmentioning
confidence: 97%
“…It is known that lipoprotein lipase enzyme (LPL) plays the key role in the regulation of lipid metabolism, especially in hydrolysis of triglycerides [12]. Although LPL gene is polymorphic, but we found only few studies on the relationship of these polymorphisms with the risk of disease development [6,7,9].…”
mentioning
confidence: 99%